Functional Analysis of an Intronic FBN1 Pathogenic Gene Variant in a Family With Marfan Syndrome - Hu, Kui; Wan, Yun; Lee, Fu-Tsuen; Chen, Jinmiao; Wang, Hao; Qu, Haonan; Chen, Tao; Lu, Wang; Jiang, Zhenwei; Gao, Lufang; Ji, Xiaojuan; Sun, Liqun; et al. (Frontiers in Genetics, 2022)
Marfan syndrome (MFS) is an autosomal dominant connective tissue disorder that canonically affects the ocular, skeletal, and cardiovascular system, in which aortic tear and rupture is the leading cause of death for MFS patients. Genetically, MFS is primarily associated with fibrillin-1 (FBN1) pathogenic variants. However, the disease-causing variant in approximately 10% of patients cannot be identified, partly due to some cryptic mutations that may be missed using routine exonic sequencing, such as non-coding intronic variants that affects the RNA splicing process. We present a 32-year female with typical MFS systemic presentation that reached to a clinical diagnosis according to the revised Ghent nosology. We performed whole-exome sequencing (WES) but the report failed to identify known causal variants when analyzing the exonic sequence. However, further investigation on the exon/intron boundaries of the WES report revealed a candidate intronic variant of the fibrillin 1 (FBN1) gene (c.248-3 C>G) that predicted to affect the RNA splicing process. We conducted minigene splicing analyses and demonstrated that the c.248-3 C>G variant abolished the canonical splicing site of intron 3, leading to activation of two cryptic splicing sites and causing insertion (c.248-1_248-2insAG and c.248-1_248-282ins). Our study not only characterizes an intronic variant to the mutational spectrum of the FBN1 gene in MFS and its aberrant effect on splicing, but highlights the importance to not neglect the exon/intron boundaries when reporting and assessing WES results. We point out the need of conducting functional analysis to verify the pathogenicity of intronic mutation, and the opportunity to re-consider the standard diagnostic approaches in cases of clinically diagnosed MFS with normal or variant of unknown significance genetic results.